Effect of Seed Priming on Germination and Growth Parameters of Kidney Bean (Phaseolus vulgaris L.) - Dhungana, Prakash; Neupane, Bipin Kumar; Pokhrel, Nishchal; Subedi, Deependra; Puri, Kiran; Bhattarai, Nitesh; Shrestha, Abhisek; Gautam, Anil (Journal of the Institute of Agriculture and Animal Science, 2025)
Seed priming is an effective pre-sowing technique to enhance germination, early growth, and stress tolerance in legumes. A field experiment was conducted at the College of Natural Resources Management, Bardibas, Nepal, from December 2023 to April 2024 for evaluating the effects of ten seed priming agents on kidney bean (Phaseolus vulgaris L.). Seeds were primed for 12 hours in tap water, untreated control, potassium nitrate (2%), titanium dioxide (2%), cow urine (10%), gibberellic acid (10 ppm), sucrose (10%), calcium oxide (0.1%), glycerol (10%), and magnesium sulphate (0.2%) and sown in a randomized complete block design with four replications. Significant differences were observed among treatments for germination, plant height, secondary branching, days to 50% flowering, and field survival by using R-Studio. Titanium dioxide (2%) achieved the highest germination (99.38%), calcium oxide (0.1%) produced maximum plant height (11.18 cm), earliest flowering (35 days), and the highest survival (37 plants plot⁻¹), while gibberellic acid (10 ppm) enhanced secondary branching (5 branches plant⁻¹). These results indicate that calcium oxide and titanium dioxide are most effective for improving early growth and stress tolerance, and gibberellic acid promotes branching. However, the study did not assess the effects of these priming agents on final yield, nutrient content, or long-term stress resilience, highlighting the need for multi-season and multi-location trials to evaluate their impact on productivity and crop performance under varying environmental conditions.